Gender differences in the comorbidity of neurological and psychological disorders in a large clinical sample of children. Issue 3 (4th May 2021) - Brandt, Valerie; Napoleone, Elisa; Patalay, Praveetha
Summary: This study aimed to establish rates and gender patterns of 25 comorbidities in 1912 children (72% male) with a neurological disorder and a comparison group ( n = 40 718, 45% male) from a large clinical records data-set in child mental health services in the UK with clinician-recorded data on neurological and psychological conditions. Obsessive–compulsive disorder, oppositional defiant/conduct disorders, autism spectrum disorders and intellectual disabilities (also known in UK health services as learning disabilities) occurred significantly more often in both boys and girls with neurological disorders than in the comparison group. Girls with neurological disorders showed a 'male-typic' comorbidity profile.